De novo transcriptome analysis of the centrohelid Raphidocystis contractilis to identify genes involved in microtubule‐based motility. (7th December 2022) - Ikeda, Risa; Sakagami, Tosuke; Hamada, Mayuko; Sakamoto, Tatsuya; Hatabu, Toshimitsu; Saito, Noboru; Ando, Motonori
Abstract: The centrohelid heliozoan Raphidocystis contractilis has many radiating axopodia, each containing axopodial microtubules. The axopodia show rapid contraction at nearly a video rate (30 frames per second) in response to mechanical stimuli. The axopodial contraction is accompanied by cytoskeletal microtubule depolymerization, but the molecular mechanism of this phenomenon has not been elucidated. In this study, we performed de novo transcriptome sequencing of R . contractilis to identify genes involved in microtubule dynamics such as the rapid axopodial contraction. The transcriptome sequencing generated 7.15‐Gbp clean reads in total, which were assembled as 31, 771 unigenes. Using the obtained gene sets, we identified several microtubule‐severing proteins which might be involved in the rapid axopodial contraction, and kinesin‐like genes that occur in gene duplication. On the other hand, some genes for microtubule motor proteins involved in the formation and motility of flagella were not found in R . contractilis, suggesting that the gene repertoire of R . contractilis reflected the morphological features of nonflagellated protists. Our transcriptome analysis provides basic information for the analysis of the molecular mechanism underlying microtubule dynamics in R . contractilis .